Pengaruh Brand Trust, Brand Image, dan Klaim Logo Tasya Farasya Approved Terhadap Keputusan Pembelian Produk Skintific Pada Generasi Z Di Kecamatan Sidoarjo - Azizy, Ailsa Rania; Arifin, Rois; Sholehuddin, Sulton (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
Abstract This research aims to determine "The Influence of Brand Trust, Brand Image, and Tasya Farasya Approved Logo Claims on the Decision to Purchase Skintific Products in Generation Z in Sidoarjo District". The type of research used in this research is quantitative research. This research sample was taken using a multistage random sampling technique, which is a sampling method in which the population in a large area is divided into several smaller areas with clear boundaries. The sample calculation uses the Lemeshow formula, namely with a total sample of 96 respondents. The analysis technique used in this research is multiple linear regression. The research results show that the results of the t test (partial) on brand trust, brand image and social media influencers partially influence purchasing decisions. Meanwhile, the research results show that the results of the F test (simultaneous) on brand trust, brand image and social media influencers simultaneously influence purchasing decisions. Keyword : Brand Trust, Brand Image, Social Media Influencers and Purchasing Decision.